Amylolytic microorganisms from diverse tropical environments: Isolation, identification, and amylase production. Issue 1 (23rd December 2021) - Muriithi, Josphine; Matofari, Joseph W.; Nduko, John M.
Abstract: This study aimed to identify microbes producing amylases from diverse unexplored environments in Kenya. Screening based on microorganisms' ability to grow on minimal media (M9) supplemented with starch resulted in the selection of 70 amylolytic isolates. The isolates were then subjected to primary screening based on starch hydrolysis ratio (SHR) obtained by halo formation on starch agar plates after flooding plates with Lugol's iodine solution. SHR narrowed down the isolates' number to 17 (SHR > 1.5), which were used for subsequent experiments. The 17 isolates were grown on M9 starch broth for the production of amylases. Crude amylases and commercial enzyme (control) were assayed for amylase activity using the 3, 5‐dinitrosalicylic acid method. Specific enzyme activities of crude enzymes ranged between 0.0079 and 0.0629 U g −1, which were lower than 1.7188 U g −1 of the control. Five enzymes with the highest specific enzyme activity were used for cassava hydrolysis. All crude enzymes exhibited higher specific enzyme activity (0.0707–0.1853 U g −1 ) than the control (0.0052 U g −1 ) in hydrolyzing cassava. Alkaline lakes had the highest number (4) of isolates whose enzymes had the highest specific enzyme activity, while isolates from potato processing plant waste, termite gut, and black soldier fly gut had a representative each. Isolates with enzymes having the highest specific enzyme activity were identified by DNA sequencing and belonged to Lysinibacillus sp. (four isolates), Alternaria sp. (one isolate), and Bacillus sp. (two isolates). The study demonstrated the presence of microorganisms in tropical environments with amylase activity that can be scaled and optimized for practical applications. Abstract : Amylolytic microbes from diverse tropical environments: Isolation, identification, and amylose production Highlights: Screening on minimal media (M9) supplemented with starch identified 70 amylolytic isolates, which were narrowed down to 17 and then 7 based on starch hydrolysis ratio and specific enzyme activity, respectively. Specific enzyme activities of crude enzymes were lower than that of the control on corn starch but higher than the control in hydrolyzing cassava. Alkaline lakes had the highest number of isolates producing enzymes with the highest specific enzyme activity and the isolates belonged mostly to Lysinibacillus sp. (by DNA sequencing).